Duodenal Diverticular Perforation after Small Bowel Obstruction: A Case Report. (7th August 2018) - Khan, Khuram; Saeed, Saqib; Maria, Haytham; Sbeih, Mohammed; Iqbal, Farhana; Ramcharan, Alexius; Donaldson, Brian
Abstract : Introduction. Duodenal diverticulum is a rare disease that can be easily missed. The incidence of duodenal diverticulum diagnosed by upper GI study is approximately 5%. Autopsy results show that 22% of the population have duodenum diverticulum. Most patients with duodenal diverticulum are asymptomatic. However, complications like inflammation, perforation with retroperitoneal abscess, sepsis, pancreatitis, bile duct obstruction, and bleeding can occur. Approximately 162 cases of perforated duodenal diverticulum have been reported in the literature. Case Presentation. We present a rare case of an 82-year-old female with perforation of a duodenal diverticulum caused by small bowel obstruction; in addition to this, there was a synchronous colonic tumor. Conclusion. Diagnosis and management of this rare disorder are controversial. Nonoperative management is advocated in some cases. Some of the cases require early aggressive surgical intervention. The mortality rate remains approximately 45% in all these patients.